Enhancing Engineering Students' skill through Project-Based Learning in ESP Class - Tri Kristianti; Hevie Dwi Novianto; Muhammad Mujtaba Asad (Jurnal Pendidikan Teknik Sipil, 2023)
Background: English for Specific Purpose (ESP) plays a significant role in developing the student's English language skills in writing, reading, speaking, and listening. In Indonesia, English has been learned since the students were in early education to a higher level, however, they are found less confident in using English for communicating especially in ESP classMethods: This research is conducted to find a suitable method to increase the student's self-confidence and enhance their language skills through the appropriate approach called Project Based Learning (PBL). This PBL focuses on the student's oral performance during the Final Test project, which employs technology to reach its purpose and it is conducted online during the pandemic. This study used Kurt Lewin's Classroom Action Research (CAR) as the research methodology consisting of planning, acting, observing, and reflecting. The subjects of this study were 30 Civil Engineering students in semester 2 of the 2020/2021 academic year. Classroom observation, interview, and teacher evaluation using the National Council Teacher of English (NCTE) Oral presentation rubric are used as the data collectionResults:  The finding shows that students' confidence increased therefore it enhanced their language skills ability through this PBL activity along with the teacher's support and motivation during the whole semester.Conclusion:  Project Based-Learning significantly affects the student's language development, including building their confidence and improving their motivation in using English contextually and creatively without fear of making mistakes. Moreover, Project Based-Learning helps the students feel relaxed and comfortable in ESP class, yet they found it challenging simultaneously.